2023
DOI: 10.1021/acsami.2c20495
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Hydrophobic Liquid Crystalline Fibers Fabricated from Defect Arrays of Reactive Mesogens via Electric Field Modulation

Abstract: We have fabricated patterned fibers using a small-molecular-weight liquid crystal (LC) and reactive mesogens (RMs) under controlled electric fields in which defect arrays are generated depending on the electrode configuration. For this, the AC electric field with interdigitated electrodes is used to develop versatile defect structures of the LC phase. Hydrophobic LC network (LCN) fibers exhibiting porous morphologies have been made by removing the LC part after the polymerization of RM. The resulting LCN fiber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Various fibril surface morphologies can be effectively realized by utilizing templates on nematic LCs with vortex and helical structures through external stimulation such as an electric field, as in this study. 3,13,23 So far, an ITO cell with a width and separation of 10 μm has been used to analyze the structural properties of the zigzag patterned fiber shown in Figures 2 and 3. It is confirmed that zigzag disclination lines can be generated irrespective of the electrode distance, provided that LCs with positive dielectric anisotropy are placed over the in-plane electric field.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various fibril surface morphologies can be effectively realized by utilizing templates on nematic LCs with vortex and helical structures through external stimulation such as an electric field, as in this study. 3,13,23 So far, an ITO cell with a width and separation of 10 μm has been used to analyze the structural properties of the zigzag patterned fiber shown in Figures 2 and 3. It is confirmed that zigzag disclination lines can be generated irrespective of the electrode distance, provided that LCs with positive dielectric anisotropy are placed over the in-plane electric field.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…LC-templated CVP studies also showed this defect-avoid phenomenon. , Therefore, in our system, it can be rationalized to have various oriented fibers by modulating LC directors or even defect structures. Various fibril surface morphologies can be effectively realized by utilizing templates on nematic LCs with vortex and helical structures through external stimulation such as an electric field, as in this study. ,, …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, when a 𝜆 plate is placed at an angle of 45°relative to the two perpendicular linear polarizers, the orientation of Cu 3 (HHTP) 2 crystals can be inferred based on the distinct colors of the POM image. [55,56] The observed negative birefringence suggests that the refractive index that is perpendicular to the long axis of the fiber-like aggregate is larger than that along the long axis. [57] Since the long axis of a fiber-like aggregate is consistent with the long crystal axis of a rod-shaped Cu 3 (HHTP) 2 crystal, the POM image suggests that the yellow and blue regions consist of Cu 3 (HHTP) 2 rods with their long crystal axes oriented parallel and perpendicular to the retardation plate, respectively.…”
Section: Alignment-induced Pattern Generationmentioning
confidence: 99%
“…These polymers retain the programmed molecular orientation established during the LC phase monomer state even after polymerization. The specially programmed polymers exhibit distinct properties compared to conventional polymers, such as controlled polymer morphology, [29][30][31] anisotropic optical properties, [32] and anisotropic actuating performance. [33,34] When fabricating composites using LC polymers, their exceptional durability against high temperatures and various solvents facilitates the incorporation of diverse inorganic materials through post-polymerization processes.…”
Section: Introductionmentioning
confidence: 99%